Bidadari Surga Dalam Tafsir Fī Ẓilāl Alquran Karya Sayyid Quṭb - Chyta, Dena Aria; Harahap, Mardian Idris; Simamora, Nur Aisah (Kamaya: Jurnal Ilmu Agama, 2024)
The interpretation of heavenly pleasures is often seen as gender biased. Some pleasures of paradise are understood to be exclusive to one gender. However, gender is not a condition for entering paradise; such interpretations are about the heavenly maidens. This study aims to explore the descriptions of heavenly maidens in the Koran and analyze Sayyid Qutb’s understanding of the Quranic verses about the heavenly maidens. The research uses a qualitative method with descriptive-analytical data analysis techniques. The findings of this study reveal that the Quran describes the physical characteristics of the heavenly maidens with the word “ḥūr” paired with “’īn,” found in Surah Ad-Dukhan verse 54, Surah At-Tur verse 20, and Surah Al- Waqi'ah verse 22. At other times, the Quran uses the more general term “azwāj” (spouses) to describe the heavenly maidens. This word is mentioned 4 times, in Surah Al-Baqarah verse 25, Surah Ali ‘Imran verse 15, Surah An-Nisa verse 57, and Surah Yasin verse 56. Furthermore, in interpreting the heavenly maidens in the Koran, according to Sayyid Qutb, the expression “heavenly maidens” needs to be understood as an indication of their existence. According to Qutb, the word “ḥūr” refers to women with fair skin, and large eyes with white and black color complementing each other. As for the phrase “qāṣirāt al-Ṭarf atrāb,” it is interpreted as the women of paradise praised by Allah for their loyalty, always lowering their gaze and never looking away except towards their spouses. The term “azwāj muṭahharah” according to Qutb signifies the state of women being devoid of the negative qualities possessed by women in worldly life.